AN EXPLORATION OF DIVIDED ATTENTION IN YOUNG ADULTS DURING READING WITH MULTITASKING ACTIVITIES: A SCIENCE PERSPECTIVE - Tul’adawiyah, Ropiah; Dahlan, Tina Hayati; Zaenulloh, Annas (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
Multitasking activities, such as listening to liked and disliked songs and eating snacks, have an impact on young adults' focus while reading. Focusing on graduate students who engage in more activities, this study addresses the effects of multitasking on academic performance. In the digital age, prevalent multitasking behaviors can negatively impact work quality and mental health. This qualitative, experimental design study involved eight graduate students, aged 24-28 years old, from a university in Bandung. The participants were selected through purposive sampling, participating in two simulated sessions involving a reading task with multitasking activities. Data were collected through self-reported journals and analyzed descriptively. Findings showed that memorable songs were more distracting than disliked songs, while snacking also affected focus but to a lesser extent. These results support the theory that attention is a limited resource that must be managed efficiently. This research discusses the single pool and multiple pool models that explain how emotional and sensory distractions affect multitasking ability. Therefore, it is necessary to understand distraction factors in educational and professional contexts. Future research could involve in-depth interviews to gain deeper insights into strategies to maintain focus, improving our understanding of divided attention and multitasking, particularly in education.